PENGARUH PENGGUNAAN EXPANSION VALVE BERBAHAN DASAR MATERIAL DENGAN KONDUKTIVITAS RENDAH TERHADAP PERFORMA AC MOBIL DINAS TNI-AD JENIS ISUZU PANTHER DENGAN VARIASI BEBAN PENDINGINAN - Wijanarko, Heri; Sugihandoko; Sukahar (PPM Sdirjianbang Akademi Militer, 2023)
Comfort in a vehicle usually uses an air conditioning system. AC is a type of machine that works following a thermodynamic cycle, namely the vapor compression cycle. A refrigeration machine depends on the ability of the compressor to meet the amount of refrigerant gas that needs to be circulated. The compressor is a tool for pumping cooling material (refrigerant) so that it continues to circulate in the system. The performance of the car's AC compressor is controlled by the thermostat, where the thermostat signals whether it is active or not active depending on whether the temperature in the car has been reached or not.This research includes variations in cooling load with a fixed compressor rotation of 759 RPM, each variation of cooling load is tested with a fixed compressor rotation of 759 RPM using one R-134a refrigerant to determine the COP, then this research is continued by calculating the on-off time of the compressor. to save energy used.The results of the research carried out show that the greater the cooling load, the greater the compressor inlet pressure and compressor outlet pressure (∆P = P1 – P2).